Potensi Produksi Tanaman Pare (Momordica charantia L.) Menggunakan POC Azolla dan AB Mix pada Sistem Deep Flow Techniaque (DFT) - Dewinka Suma; Arianto Sapu; Yusuf La’lang Limbongan; Willy Yafet Tandirerung (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
The research project is titled Production Potential of Bitter Melons (Momordica charantia L.) Using POC Azolla and AB Mix on the Deep Flow Technique (DFT) System was carried out in Bungin, North Makale District, Tana Toraja Regency from May to August 2025. This study aims to determine the economic potential of bitter melon plants by providing AB Mix and POC Azolla nutrients in hydroponic methods and analyze the best influence of these nutrient combinations on the growth and production of bitter melon plants. The research method used was a Group Random Design (RAK) with four treatments, namely 100% AB Mix, AB Mix 80% + POC Azolla 20%, AB Mix 70% + POC Azolla 30%, and AB Mix 60% + POC Azolla 40%. The results of the study showed that P1 treatment (AB Mix 80% + POC Azolla 20%) had the best influence on the vegetative and generative growth of bitter melon plants. This treatment results in a higher average plant height, leaf count, and fruit weight than other treatments. This proves that the combination of Azolla liquid organic fertilizer (POC) with AB Mix is able to provide a balance of nutrients that support photosynthesis, tissue formation, and fruit quality. In addition, the application of the DFT hydroponic system has been proven to increase the efficiency of water and fertilizer use, reduce the risk of soil pest attacks, and produce more hygienic bitter melon products. These findings show that hydroponic cultivation innovation with the use of POC Azolla can be a sustainable solution in supporting food security while being environmentally friendly. Thus, this research makes an important contribution to the development of modern agricultural technology, especially in optimizing the production of vegetables with high economic value.